PEMBELAJARAN DIGITAL MARKETING BAGI PELAKU USAHA KECIL MENENGAH DIDESA GUNUNG SELAN - Puspita, Popi; Labo, Den Syahrudin; Lesmana, Dedi; Oktridarti, Levy (Jurnal PADAMU NEGERI (Pengabdian pada Masyarakat Bidang Eksakta), 2021)
With the digital world expanding into the marketing sector, UMKM need to adapt to the digital world. The benefits of UMKM being able to access online by being involved in the digital world and developing capabilities in using the marketplace are significant business benefits both in terms of income, job opportunities, innovation and competitiveness (Jannatin et al., 2020). As a digital marketing medium that is currently in great demand, one of them is Instagram. Where many people from various circles of our society have used the Instagram application as a communication medium and as an application for shopping. So we also want to encourage small and medium businesses to use Instagram media for product sales activities